Determination of the effective load-bearing cross-section of sintered steel products - Godec, Matjaž (Materiali in tehnologije, 2003)
The mechanical properties of sintered steel products depend mostly on their porosity and the bonds between the steel powder particles. Increasing the cohesion interconnection significantly improves the mechanical properties. Using scanning electron microscopy (SEM) with its high depth resolution it is possible to determine the fraction of ductile fracture which is honeycomb-like in appearance and is effective load-bearing cross-section.
Keywords: jekla; sintranje; mehanske lastnosti; prelomi; mikrostruktura